Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/ele.13966
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Eltonian shortfall with trait‐based interaction models

Abstract: We have very limited knowledge of how species interact in most communities and ecosystems despite trophic relationships being fundamental for linking biodiversity to ecosystem functioning. A promising approach to fill this gap is to predict interactions based on functional traits, but many questions remain about how well we can predict interactions for different taxa, ecosystems and amounts of input data. Here, we built a new traits‐based model of trophic interactions for European vertebrates and found that ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 61 publications
7
21
0
Order By: Relevance
“…In all cases, the predicted connectance was greater than the observed connectance (Figure 5b). This result is similar to that of a recent study of European vertebrate food webs by Caron et al (2022). They found that local food web connectance was consistently overestimated by a trait‐based model which used diet, nesting habitat, activity time, foraging behavior, and body mass of species.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In all cases, the predicted connectance was greater than the observed connectance (Figure 5b). This result is similar to that of a recent study of European vertebrate food webs by Caron et al (2022). They found that local food web connectance was consistently overestimated by a trait‐based model which used diet, nesting habitat, activity time, foraging behavior, and body mass of species.…”
Section: Discussionsupporting
confidence: 93%
“…In all cases, the predicted connectance was greater than the observed connectance (Figure 5b). This result is similar to that of a recent study of European vertebrate food webs by Caron et al (2022).…”
Section: Connectance and Missing Linkssupporting
confidence: 92%
See 2 more Smart Citations
“…When possible, MSC analyses should test the sensitivity of connectivity estimates by comparing models that vary the presence-absence and strength of interactions to better understand the relative impact of these two sources of error. Promising new studies on metawebs, which aim to understand spatial variation in food web structure, find that interactions can be grouped into trophic guilds using functional traits with relatively little error (O'Connor et al, 2020;Caron et al, 2022). Such studies can help bridge the gap between spatial community ecology and landscape ecology, a link that is currently missing in applied connectivity conservation (Pollock et al, 2020).…”
Section: Integrating Species Interactionsmentioning
confidence: 99%